Proceedings of the Fourth Italian Conference on Computational Linguistics CLiC-it 2017 : 11-12 December 2017, Rome - Roberto Basili
This book presents the proceedings of the annual Conference of Computational Linguistics (CLiC-it), which aims to provide a forum for discussion in the field of computational linguistics. The proceedings include interventions on the automatic treatment of language, with theoretical and methodological reflections on the subject, and provide an important contribution to this field of research. The other main topics are: computational linguistics, linguistics, cognitive sciences, automatic learning, computer science, knowledge representation, information retrieval and digital humanities. The organization of the conference is the result of the effort of the Italian Association of Computational Linguistics (AILC http://www.ai-lc.it/), represented every year by some of the organizing members, who are also affiliated to other organizations operating in the field of computational linguistics.